Hybrid Dual-Loop Control for Current Regulation and Low-Frequency Ripple Rejection in Led Drivers - Menke, Maikel F. (2021)
This paper presents a new hybrid dual-loop control system for the DC/DC LLC resonant converter, operating as a downstream DC/DC converter in a two independent stage offline LED driver. The outer loop employs a PI controller to maintain the average LED current regulated at the reference value and reject parametric variation. The inner loop implements an adaptive periodic disturbance rejection (APDR) subsystem, thus conceiving the hybrid PI&APDR controller. The APDR subsystem is designed to strictly reject the bus voltage ripple and limit its transmission to the LED current. Experimental results show the proposed controller feasibility in achieving good tracking behavior, reduced output current ripple under different bus voltage ripple amplitude and frequency, robustness against parametric variations, and simple implementation and design. For the sake of completeness, the proposed PI&APDR is compared with the conventional proportional resonant controller employing experimental results and extra analysis based on simulations.